2012
DOI: 10.1073/pnas.1119908109
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of fructokinase C and A isoforms on fructose-induced metabolic syndrome in mice

Abstract: Fructose intake from added sugars correlates with the epidemic rise in obesity, metabolic syndrome, and nonalcoholic fatty liver disease. Fructose intake also causes features of metabolic syndrome in laboratory animals and humans. The first enzyme in fructose metabolism is fructokinase, which exists as two isoforms, A and C. Here we show that fructose-induced metabolic syndrome is prevented in mice lacking both isoforms but is exacerbated in mice lacking fructokinase A. Fructokinase C is expressed primarily in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
294
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(319 citation statements)
references
References 38 publications
(49 reference statements)
21
294
1
3
Order By: Relevance
“…Without negative feedback mechanisms, metabolic flow of fructose through this pathway remains largely unregulated and greatly exceeds energy demands (4,7). This causes dramatic stimulation of lipogenesis and fat accumulation in the liver, Recently, Ishimoto et al (10) demonstrated that fructoseinduced, abnormal lipogenesis in the liver, hepatosteatosis, triglyceridemia, and visceral obesity were absent in mice lacking both isoforms of KHK. While consuming similar amounts of fructose, KHK-deficient mice were excreting substantial amounts of it with urine but still maintained positive energy balance but on the lower level than wild-type (WT) mice fed with fructose (10).…”
mentioning
confidence: 99%
“…Without negative feedback mechanisms, metabolic flow of fructose through this pathway remains largely unregulated and greatly exceeds energy demands (4,7). This causes dramatic stimulation of lipogenesis and fat accumulation in the liver, Recently, Ishimoto et al (10) demonstrated that fructoseinduced, abnormal lipogenesis in the liver, hepatosteatosis, triglyceridemia, and visceral obesity were absent in mice lacking both isoforms of KHK. While consuming similar amounts of fructose, KHK-deficient mice were excreting substantial amounts of it with urine but still maintained positive energy balance but on the lower level than wild-type (WT) mice fed with fructose (10).…”
mentioning
confidence: 99%
“…We use the apparent self-contradiction, -a calorie is not a calorie‖, to emphasize that different nutrients with the same amount of food energy (calories) can differ in their effects on body weight. Fructose, for example, increases appetite more effectively than glucose [20,26]. One calorie of fructose is therefore more obesogenic than one calorie of glucose.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…As a major component of added sugars, high intake of fructose has been shown to cause numerous adverse metabolic effects, suggesting that it has a contributory role in the development of obesity and metabolic syndrome [6][7][8]. Administration of added sugars or fructose has been shown to induce all of the features of metabolic syndrome in rats and in humans, such as hypertriglyceridemia and lipogenesis, increased blood pressure, fatty liver, and visceral fat accumulation [9][10][11]. Fructose has also been shown to impair insulin sensitivity, injure β-islet cells, and cause lactic acidosis, oxidative stress, and kidney injuries in animals [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%